Verbal Expedients and Transformative Utterances in Episodes of Egils saga Skallagrimssonar. - Sayers, William (Scandinavian Studies)
The article discusses the performative utterances and verbal expedient in two episodes of "Egils saga Skallagrimssonar" that appear to reflect an objective reality but alternative subjective view. It discusses scenes from an episode entitled “Hamhleypa-Skaldik als Verwandlungskunst: Zur ‘Hpfudlausn' as evaluated by Phillip Theisohn. Another episode “Caoilte in Iceland: Gaelic Folklore" as evaluated by Michael Chesnutt is included.